Quality cultures in higher education institutions: development of the quality culture inventory - Hildesheim, Christine; Sonntag, Karlheinz (Geographies of the University, 2018)
Quality assurance and quality management are central challenges in the governance of higher education institutions. In this context, the importance of promoting an institution-specific quality culture has drawn increasing attention. The concept of quality culture expands traditional approaches to quality assurance by focusing on aspects of organizational psychology, such as shared attitudes and commitment to quality. Despite growing discussion of quality culture, sound empirical approaches that capture this key construct have not been developed systematically. This chapter summarizes the theoretical background and selected results of the heiQUALITY Cultures project, which aimed at creating an empirical instrument that operationalizes quality culture within institutions of higher education. Extensive research resulted in the development of the Quality Culture Inventory (QCI), the first approach to allow institutions of higher education to assess their current state of quality culture empirically. The results of the QCI constitute a solid basis for reflecting on quality culture and developing focused measures for improving it.
Gesehen am 10.12.2018